The Equation of Brazilianness in “Alegria, alegria”: An Overview and Formal Aspects (Orfeu, 2021)
The core of this paper is an analysis of the song “Alegria, alegria” by Caetano Veloso, focusing on formal aspects of a particular depiction of brasility in local commercial radiophonic music during the sixties. We indicate how this song, a proponent in III Festival de Música Popular Brasileira, in 1967, and a kind of first-hour manifest for the aesthetic program of Tropicália, suspends a canonic reading of brasility by means of tensioning the conceptual antithetic pairs archaic/modern and local/universal. To introduce the argument, we go through the details of procedures we have called multidirectioning and juxtaposition, operating through the musical and poetic strata. Based on the presented elements, we highlight, at last, how “Alegria, alegria” engenders, in its very structure, conflicts that inflect the debate of brasility before the global influx of mass culture.
Keywords: Alegria, alegria; Tropicália; Brasility; Popular Music; Analysis